Proceedings of the Ocean Drilling Program 1989
DOI: 10.2973/odp.proc.sr.108.145.1989
|View full text |Cite
|
Sign up to set email alerts
|

Rock-Magnetic Stratigraphy of Leg 108 Sites 658, 659, 661, and 665, Eastern Tropical Atlantic

Abstract: The results of detailed rock-magnetic measurements of selected stratigraphic intervals at Ocean Drilling Program Leg 108 Sites 658, 659, 661, and 665 are as follows:1. At Site 658, it is likely that the entire interval was extensively affected by reductive diagenesis, resulting in the loss of fine-grained magnetite. At Sites 659 and 665, we suspect that a similar diagenetic alteration of fine-grained magnetite occurred, but that it was confined to discrete intervals. At Site 661, the uppermost 60-70 mbsf of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The advent of this magnetometer has been a boon for shipboard paleomagnetic study and allows whole cores or split core to be measured rapidly. Scientific results from Leg 104 (Bleil, 1989), Leg 105 (Clement et al , 1989), Leg 108 (Tauxe et al , 1989) and Leg 115 (Schneider and Kent, 1990) indicate that the pass‐through magnetometer is capable of producing very high quality magnetostratigraphic records. However, the whole‐core measurements suffer from physical disturbance of the core, rust contamination and pervasive remagnetization often associated with core barrels.…”
Section: Magnetostratigraphymentioning
confidence: 99%
“…The advent of this magnetometer has been a boon for shipboard paleomagnetic study and allows whole cores or split core to be measured rapidly. Scientific results from Leg 104 (Bleil, 1989), Leg 105 (Clement et al , 1989), Leg 108 (Tauxe et al , 1989) and Leg 115 (Schneider and Kent, 1990) indicate that the pass‐through magnetometer is capable of producing very high quality magnetostratigraphic records. However, the whole‐core measurements suffer from physical disturbance of the core, rust contamination and pervasive remagnetization often associated with core barrels.…”
Section: Magnetostratigraphymentioning
confidence: 99%
“…A general correlation between the sub-bottom depth at which these diagenetic processes occurred and the local organic productivity was suspected, but low total organic carbon (TOC) contents precluded shipboard evaluation of this relationship. Microbially driven reduction of magnetite has been reported by several authors (e.g., Karlin and Levi, 1983;van Vreumingen, 1984;Bloemendal et al, 1989). Sager (1988) suspected that a metastable magnetic iron sulfide, either greigite or pyrrhotite, had been generated in Leg 101 sediments, and that this phase was the carrier of an overprint.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid this problem, two holes are drilled so that by measuring physical parameters such as magnetic susceptibility in each hole, it is possible to correlate between holes and reconstruct the true thickness of the sedimentary pile. Numerous workers have, since ODP Leg 108 (Bloemendal et al, 1988(Bloemendal et al, , 1989) developed a routine procedure on all ODP legs to obtain these results from whole core magnetic susceptibility (see, for example, Ruddiman, Sarnthein, Baldauf, et al, 1988;Mascle, Moore, et al, 1988;Backman, Duncan, et al, 1988;Cochran, Stow, et al, 1989;Prell, Niitsuma, et al, 1989;Peirce, Weissel et al, 1989;Rangin, Silver, von Breymann, et al, 1990). It is far beyond the scope of this paper to present an extensive review of this technique, which can be found with the appropriate references in Robinson (1993).…”
Section: The Use Of Downhole Susceptibility Logs To Evaluate the Truementioning
confidence: 99%